ChemInform Abstract: Cyclization and Annulation Reactions of Nitrogen‐Substituted Cyclopropanes and Cyclobutanes. Issue 41 (7th October 2014) - de Nanteuil, F.; De Simone, F.; Frei, R.; Benfatti, F.; Serrano, E.; Waser, J.
Abstract Review: [46 refs.